2010
DOI: 10.1177/0363546510382858
|View full text |Cite
|
Sign up to set email alerts
|

Improved Corticosteroid Treatment of Recalcitrant de Quervain Tenosynovitis With a Novel 4-Point Injection Technique

Abstract: In high-resistance training athletes, recalcitrant DQT responds more favorably to the novel point 4 technique than to the standard 2-point injection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…De Quervain's tenosynovitis most commonly arises due to the overuse of the thumb musculature which is characterized by pain that spread over the surface of radial aspect of the wrist and intensified by ulnar deviation of the hand 16 . The prevalence of this condition upturns with new occupational demands such as extended work at computer, an athlete especially who follows a high resistance training that includes lifting weight and using hands for support and maximal exertion 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Quervain's tenosynovitis most commonly arises due to the overuse of the thumb musculature which is characterized by pain that spread over the surface of radial aspect of the wrist and intensified by ulnar deviation of the hand 16 . The prevalence of this condition upturns with new occupational demands such as extended work at computer, an athlete especially who follows a high resistance training that includes lifting weight and using hands for support and maximal exertion 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The examiner stabilized the forearm and passively deviated the wrist. Pain at the radial wrist, over the Abductor polli-cis longus and Extensor pollicis brevis tendons, a positive test indicated, when it is significantly more tender than the uninvolved side 5,10 . A written consent was signed by the authorities of institution before the survey was conducted and as quoted by Dr. Padulo in his editorial "Basic principles and recommendation in clinical and field research" informed verbal consent was taken from the study participants according to the "Declaration of Helsinki" 11 .…”
Section: N= (Z) 2 X P (1-p) Dmentioning
confidence: 99%
“…De Quervain's tenosynovitis most commonly arises due to the overuse of the thumb musculature which is characterized by pain that spread over the surface of radial aspect of the wrist and intensified by ulnar deviation of the hand 16 . The prevalence of this condition upturns with new occupational demands such as extended work at computer, an athlete especially who follows a high resistance training that includes lifting weight and using hands for support and maximal exertion 10 . In 2010, a case report of bilateral De Quervain's tenosynovitis revealed that the diagnosis linked the patient's condition with excessive routine of the text messaging feature on a cellular telephone 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The examiner stabilized the forearm and passively deviated the wrist. Pain at the radial wrist, over the Abductor pollicis longus and Extensor pollicis brevis tendons, a positive test indicated, when it is significantly more tender than the uninvolved side 5,10 . A written consent was signed by the authorities of institution before the survey was conducted and as quoted by Dr. Padulo in his editorial "Basic principles and recommendation in clinical and field research" informed verbal consent was taken from the study participants according to the "Declaration of Helsinki" 11 .…”
Section: Methodsmentioning
confidence: 99%
“…He concluded that 4-point injection gave superior results than 2-point injection technique in recalcitrant De Quervain's disease. 24 Even though some studies have reported superior results with two or four point injection technique it is additionally painful and the landmarks are not clearly made out. Our study has given a result of 87.5% success rate with single injection of triamcinolone injection, which is on par with other reported study.…”
Section: Injection Techniquementioning
confidence: 99%